2017
DOI: 10.1038/ncomms15354
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric holograms based on a topological insulator material

Abstract: Holography has extremely extensive applications in conventional optical instruments spanning optical microscopy and imaging, three-dimensional displays and metrology. To integrate holography with modern low-dimensional electronic devices, holograms need to be thinned to a nanometric scale. However, to keep a pronounced phase shift modulation, the thickness of holograms has been generally limited to the optical wavelength scale, which hinders their integration with ultrathin electronic devices. Here, we break t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 29 publications
1
74
0
Order By: Relevance
“…Using this mean value, thicknesses as both a function of dose at a fixed angle and as a function of angle at a fixed dose can be determined using equation (5). Error values are calculated using the upper and lower values of n. Figure 6 shows the determined thicknesses of doses from 100 Lm -1000 Lm at the narrowest reflection angle of 31°.…”
Section: Results and Preliminary Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Using this mean value, thicknesses as both a function of dose at a fixed angle and as a function of angle at a fixed dose can be determined using equation (5). Error values are calculated using the upper and lower values of n. Figure 6 shows the determined thicknesses of doses from 100 Lm -1000 Lm at the narrowest reflection angle of 31°.…”
Section: Results and Preliminary Data Analysismentioning
confidence: 99%
“…4 Recently it has been demonstrated that a detailed knowledge of the refractive index of a material is important in the design of holographic devices. 5 In contrast to inorganic materials, organic materials are relatively poorly studied. 6 Optical properties of ices are of particular interest to the astrochemical community.…”
Section: Introductionmentioning
confidence: 99%
“…The cladding is realised by the atomic layer deposition (ALD) of ∼110 nm of antimony telluride (Sb 2 Te 3 ) thin films . This material is chosen because of its high refractive index of 5 and good transparency at mid‐IR wavelengths (for experimental details, see Experimental section, Supporting Information Figures S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…The growth rate was 0.01 nm per cycle. The X‐ray diffraction (XRD) and Raman spectrum reveal the high quality of the ALD grown Sb 2 Te 3 thin film …”
Section: Methodsmentioning
confidence: 99%
“…Recently, strong interference effect in highly absorptive media is proposed for realizing wide‐angle spectral selective absorbers and light harvesting devices . These studies show that the strong nanocavity interference occurs within a stack of layers composed of ultrathin lossy materials and metallic substrates.…”
mentioning
confidence: 99%